Analysing the impact of climate change on dairy farming as perceived by the women farmers: Application of analytical hierarchy process - REDDY, DADIMI ANILKUMAR; GARAI, SANCHITA; MAITI, SANJIT; K V, MANJUNATH (The Indian Journal of Animal Sciences, 2024)
Impact of climate change on various sectors across the globe is quite evident and the dairy sector is no exemption to the threats of changing climate. Most of the activities in dairy farming are performed by women. Dairy farming is a source of sustainable income for the women in rural areas. Women are more vulnerable to the adverse effects of climate change due to their socio-economic position in the society. So, an attempt was made to capture the impacts of climate change on dairy farming from women farmers’ perspective. A total of 360 women farmers were approached for the study. Analytical hierarchy process was used to identify which of the four components and 16 sub-components of dairy farming are most affected due to changing climate. Analysis of farmers’ responses revealed that productive performance was perceived to be the most affected component and average daily milk yield was perceived to be greatly affected due changes in climate.